Thẩm định phương pháp phân tích định lượng Famotidin trong huyết tương Thỏ / Phan Thị Huyền Vy, Bùi Minh Thy, Phùng Thị Kim Huệ, Nguyễn Xuân Thành, Triệu Nguyên Trung - Phan, Thị Huyền Vy
As delivery systems of bacterial cellulose are usually used for famotidine, which is a gastrointestinal drug, acting as H2-receptor blocker, to improve its inherent low bioavailability; the created BC-networks ensured the drug prolonged-release therapy, the bioavailability of famotidine loaded in such BC-networks were evaluated by quantitative determination of famotidine in biological fluids, specifically rabbit’s plasma by HPLC. The method was validated for specificity and selectivity, calibration and linearity, limit of detection, precision and accuracy, extraction recovery,…